If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2tanxcos * x + -1 = 0 Multiply acnostx * x 2acnostx2 + -1 = 0 Reorder the terms: -1 + 2acnostx2 = 0 Solving -1 + 2acnostx2 = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 2acnostx2 = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 2acnostx2 = 0 + 1 2acnostx2 = 0 + 1 Combine like terms: 0 + 1 = 1 2acnostx2 = 1 Divide each side by '2cnostx2'. a = 0.5c-1n-1o-1s-1t-1x-2 Simplifying a = 0.5c-1n-1o-1s-1t-1x-2
| 2w-3=3w | | 5/4=45/x | | h-48/g | | 132.49+15w=192.49 | | 17a-2b+3c=-107 | | 15-0.33y=x+17 | | 5x-165=45-2x | | 6y+(-5)=(-23) | | -8/3*-2 | | 4m-4=2(2m) | | a=-16+3b+-2c | | 5(h+3)+2(h-2)=11-3(12-5h) | | 2(m-3)=8 | | Y-5=-8/3(x-2) | | 9+2v=-v | | Y=65x+0.10 | | 2.464cosx-x=2.5843 | | 7x+9=3x+8 | | -a/10=-16 | | a-3b+2c=-16 | | Y=65+0.10 | | 3(w+1)=9 | | 2.464cosx-x=205843 | | 47-3=6y | | 6x-79=12x+47 | | 1/3y-6=1/10y | | 6(2f+4)=2(3f-6) | | x+6*x-1= | | 1c+4.8=8 | | 2/3x-18=6 | | 7(x+8)=(7x+42) | | 2x-7=x-7 |